Profile of Children with Migraine - Aydin, Mustafa; Kabakus, Nimet; Bozdag, Senol; Ertugrul, Sabahattin (Springer India, 2010)
To assess the clinical characteristics of patients with migraine. The medical records of 76 patients diagnosed with migraine were reviewed using the ICHD-II 2004 diagnosis criteria. The patients were classified into three age groups: 3-6 yr olds (group I), 7-12 yr olds (group II), and 13-17 yr olds (group III). Migraine was the most common cause of headache in the patients of present pediatric neurology outpatient clinic (57.1%, 76/133). The mean age of patients was 11.08 +/- 3.27 (3.25-17) yrs. The number of girls as the age increased (groups II and III). The mean headache attacks rate was 2.5 +/- 1.5 per wk, which resulted in worsening of school performance (n = 26, 34.2%). In the majority of patients (n = 54, 71.1%), there was a family history of migraine or headache in the close relatives. Prophylaxis was found effective for all given medications (flunarizine: 46/54, propranolol: 19/21, topiramate: 10/10, sodium valproate: 1/1). These findings indicate that: (a) migraine is the most frequent cause of headache in pediatric patients, (b) it has negative effects on school performance and daily activities, (c) the family history is important for making the diagnosis and (d) prophylaxis is significantly effective.
Keywords: Children; Headache; Migraine; Prevalence; Prophylaxis